Why the Armchair in the First Place? Then Why Get up from It? (And Why Did Some Remain Seated?). Issue 3 (27th October 2016) - Kenny, Robert
Abstract : Charles Lyell advised young geologists that to discover the nature of the bigger world required travel. In the field of the natural science this had its exemplars inspired by Humboldt, Darwin, Wallace, Joseph Hooker; in the field of geography it had the model of Cook's explorations. Yet by the mid‐century even in the discipline of geography it was the armchair theorist who held sway. British anthropology came into being at the time the armchair was at its zenith, when the theorists in their studies understood that those out there on the ground could not see the forest for the trees. It claimed the perspective of the centre was required to bring order to all the observations. This article argues that the discoveries of the eighteenth century and nineteenth century existentially challenged the European view of humanity and that the aim of stay‐at‐home British ethnological research was to retrieve a history of being human. However out on the colonial frontier, the prerogative of the ethnographer became increasingly the Indigenous presence they confronted. The trees were more important than the forest. The information they sent back, backed by the authority of contact undermined the authority of the long perspective of the armchair, which was increasingly riven by contradictions and absurdities until it looked like no perspective at all. But the metropole still claimed ascendency as Alfred Haddon's expedition of 1898, laden down with the instruments of the psychology laboratory set out to confirm grand theories. It found instead that effective method in anthropology was to seek familiarity with a people, the method already employed by the colonial ethnographers.